Major Julius F. Giese giving a speech to a crowd during the July 4th celebration, Nome, Alaska, 1901. - Hegg, Eric A., 1867-1948 (1901)
Caption on image: "Major J.F. Giese Yukon pioneer making some appropriate remarks at the close of program. Nome. July 4, 1901" Original image in Hegg Album 5, page 12. Original photograph by Eric A. Hegg 1837; copied by Webster and Stevens 233.A